Adherence to malaria treatment and its contributing factors - Rita Graziella Ferreira; Rosemeiry Capriata de Souza Azevedo; Annelita Almeida Oliveira Reiners; Taísa Guimarães de Souza; Cor Jesus Fernandes Fontes (Universidade Federal de Goias, 2014)
This exploratory, descriptive and cross-sectional study was performed with the objective to estimate the frequency of adherence to malaria treatment in the Brazilian district of Três Fronteiras, belonging to the municipality of Colniza, in the state of Mato Grosso, and describe the contributing factors. Twenty-seven patients were selected by active search. Interviews were conducted for data collection, and treatment adherence was measured considering the patients' self report and by counting medication. The frequency of adherence was 77.8%. Among the factors that contributed to malaria treatment adherence, those related to the patient, particularly regarding the will to get better and the confidence in the effectiveness of the medication were the most prevalent. The identify adherence frequency rate was lower than that reported in previous studies performed in endemic regions of Brazil. In conclusion, health education actions addressing the importance of treatment adherence must be emphasized and intensified to minimize or eliminate treatment abandonment. Descriptors: Malaria; Medication Adherence; Therapeutics; Nursing Care.